The role of artificial intelligence algorithms in information systems research: a conceptual overview and avenues for research - David Bendig; Antonio Bräunche (Management Review Quarterly, 2024)
Abstract Artificial intelligence (AI) has made remarkable progress in the past decade. Despite the plethora of AI research, we lack an accrued overview of the extent to which management research uses AI algorithms. The context, purpose, and type of AI used in previous work remain unknown, though this information is critical to coordinating, extending, and strengthening the use of AI. We address this knowledge gap with a systematic literature review (SLR), focusing on 12 leading information systems (IS) journals and leveraging a customized generative pre-trained transformer (GPT) in our analyses. We propose a conceptual framework comprising eight dimensions to categorize our findings in terms of application areas, methods, and algorithms of applied AI, mitigating the lack of a concise AI taxonomy. Thus, we identify and discuss trends, outline underrepresented algorithms with significant potential, and derive research avenues. We extend the literature with a conceptual overview that may serve as a building block for theory building and further exploration of the evolving AI research domain.
Additional information: O30;O31;O33
Keywords: 330; Artificial intelligence; Machine learning; Deep learning; Generative Artificial Intelligence; ChatGPT